Screening for Alternaria leaf blight disease in breeding lines of sunflower (Helianthus annuus L.): Screening for Alternaria leaf blight disease in breeding lines of sunflower (Helianthus annuus L.) - VIKAS V KULKARNI; POORNIMA; VIJAYKUMAR GHANTE; M R UMESH (Journal of Oilseeds Research, 2020)
Several pathogens attack sunflower crop and among them sunflower leaf blight disease caused by Alternaria helianthi is major one in kharif season infecting from seedling to seed filling stage. The screening of 75 sunflower breeding lines revealed that PM6, PM160, PM26, PM163 recorded resistant reaction with PDI (percent disease index) of 4%, 3.3%, 3.1% and 7% respectively. These breeding lines can be used as resistant source in developing resistant hybrids for Alternaria leaf blight after confirming the resistance in artificial epiphytotic conditions.